Bibliografie Sądecczyzny (PDF 3,63 MB) (Książnica Śląska, 2025)
The author presents the history of the Sądecka Public Library relatedto administrative changes. Against this background, she discusses regional bibliographic activity covering various territorial areas of theSądecczyzna region. She recalls the first retrospective bibliographyof Kazimierz Golachowski, further the bibliography of WładysławaLubasiowa, the bibliographic file of Stanisław Chrząstowski and materials published in regional magazines. The text describes the current bibliographic activities carried out within the Regional Bibliography of Małopolska.